Pelatihan Mitigasi Bencana Kepada Perangkat Nagari Sungai Janiah Dan Kelompok Masyarakat Di Kabupaten Solok Provinsi Sumatera Barat - Nina Ismayani; Hary Febrianto; Nanda Okta Vianda (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
This extension activities is one of the important stages of community service activities as part of the implementation of Tridharma Perguruan tinggi. Community service activities are organized in cooperation with the community, especially to the community, and the device Nagari Sungai Janiah. With the use of an individual approach and the classical style that was used at the time of the provision of material and theory about the training of disaster mitigation of volcanic eruption and other disasters to be continued eruption of the volcano. The methods applied in the form of lectures (submission of materials by the speaker directly) varies. The results of Community service activities that participants can understand on how to save yourself the time of the occurrence of a disaster-flood, flood, earthquake, and volcanic eruption